UNVEILING THE NEXUS OF WORK INTEREST, SELF-POTENTIAL AND INDUSTRIAL WORK PRACTICE EXPERIENCE WITH THE WORK READINESS OF ACCOUNTING STUDENTS IN VOCATIONAL SCHOOLS - Fitria, Aida; Susanti, Santi; Fauzi, Achmad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to determine the effect of work interest, self-potential and industrial work experience on students' work readiness. The population in this study were accounting students at Public Vocational High School in Central Jakarta. The sampling technique in this study used proportional random sampling with a sample of 121 respondents. The method used in this study is quantitative using questionnaires and surveys. The analysis methods in this study are descriptive statistical tests, validity tests, reliability tests, normality tests, linearity tests, multiple regression tests, hypothesis tests (t-test and f-test) and determination coefficient tests. The results of the research that has been conducted state that work interest, self-potential and industrial work experience have a positive and significant effect on work readiness both simultaneously and partially.